From best practice to best fit: A framework for designing and analyzing pluralistic agricultural advisory services worldwide - Birner, Regina; Davis, Kristin E.; Pender, J.L.; Nkonya, Ephraim M.; Anandajayasekeram, P.; Ekboir, Javier M.; Mbabu, A.N.; Spielman, David J.; Horna, D.; Benin, Samuel; Cohen, M. (Informa UK Limited, 2009)
The article provides a conceptual framework and discusses research methods for analyzing pluralistic agricultural advisory services. The framework can also assist policy-makers in identifying reform options. It addresses the following question: Which forms of providing and financing agricultural advisory services work best in which situation?